PENGARUH MOTIVASI KERJA INTRINSIK, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KSP CREDIT UNION DHARMA PRIMA KITA - Prayekti; Godrikus S. Patas (Majalah Ilmiah METHODA, 2020)
Performance as the results of work functions or activities of a person or group in an organization within a certain period of time at KSP Credit Union Dharma Prima Kita. This study aims to partially determine the effect of work motivation, work environment and work discipline on employee performance. The subjects of this study were employees of KSP Credit Union Dharma Prima Kita, with a total of 70 respondents. This study uses a quantitative approach with multiple linear regression data analysis techniques and uses the SPSS for windows 25 computer program. The results of this study indicate that work motivation has a positive and significant effect on employee performance, the work environment has a positive and significant effect on employee performance, work discipline has a positive effect. and significant on employee performance and simultaneously work motivation, work environment and work discipline have a positive and significant effect on employee performance.